1983
DOI: 10.1128/iai.41.1.106-113.1983
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the adhesive properties of Neisseria meningitidis for human buccal epithelial cells and erythrocytes

Abstract: The ability of clinical and carrier isolates of Neisseria meningitidis to adhere to human buccal epithelial cells and erythrocytes was investigated. Four of the 10 fimbriated strains were able to hemagglutinate. Serial subculture of three of these strains resulted in a loss of ability to hemagglutinate and was coincident with a loss offimbriation. Other fimbriated strains were unable to hemagglutinate but did adhere to buccal epithelial cells. Subculture of one of these strains for as many as 42 passages did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…According to our results obtained with purified PilC2 protein or piliated gonococci, the potential host cell receptor for pili/PilC is a protein and sugar components do not seem to be involved in the interaction. These data are consistent with observations from other groups who found that a eukaryotic protein or glycoprotein could be a potential pilus receptor, whereas sugar structures are not involved in binding (Watt and Ward, 1977;Trust et al, 1983;Jonsson et al, 1994). In contrast, Buchanan and colleagues could inhibit the adherence of piliated gonococci by host cell treatment with various gangliosides or exoglycosidases (Buchanan et al, 1978).…”
Section: Discussionsupporting
confidence: 89%
“…According to our results obtained with purified PilC2 protein or piliated gonococci, the potential host cell receptor for pili/PilC is a protein and sugar components do not seem to be involved in the interaction. These data are consistent with observations from other groups who found that a eukaryotic protein or glycoprotein could be a potential pilus receptor, whereas sugar structures are not involved in binding (Watt and Ward, 1977;Trust et al, 1983;Jonsson et al, 1994). In contrast, Buchanan and colleagues could inhibit the adherence of piliated gonococci by host cell treatment with various gangliosides or exoglycosidases (Buchanan et al, 1978).…”
Section: Discussionsupporting
confidence: 89%
“…CD147 is expressed on different cell types, such as erythrocytes and epithelial cells. Pilus-dependent interactions between meningococci and erythrocytes, causing hemagglutination, have been documented in vitro 35,36 , and meningococci have been described crossing polarized epithelia, indicating that meningococcus might interact with CD147 in a variety of cell types. Notably, several viruses, including HIV-1, severe acute respiratory syndrome coronavirus 37 and measles virus 38 , as well as the bacterial pathogen Listeria monocytogenes 39 , also target CD147 to adhere to and/or invade epithelial cells, indicating that CD147 constitutes an evolutionarily conserved efficient target for pathogens to infect tissues and spread within organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Pili (fimbriae), the filamentous protein structures which radiate from the surface of the bacteria, have been shown to mediate interactions of both N. meningitidis and N. gonorrhoeae to mucosal epithelial celis (Craven and Frasch, 1978;McGee and Stephens. 1984;Virji and Everson, 1981;Ward and Watt, 1975) and to erythrocytes (Trust et al, 1983). In addition, increased toxicity of the piliated organisms for the epithelial cells has also been reported (Stephens ef a/., 1988a).…”
Section: Introductionmentioning
confidence: 97%